Overexpression of CD44v8-10 in Colon Polyps-A Possible Key to Early Diagnosis - Dastych, Milan; Hubatka, Frantisek; Turanek-Knotigova, Pavlina; Masek, Josef; Kroupa, Radek; Raška, Milan; Turanek, Jaroslav; Prochazka, Lubomir (Pathology oncology research, 2021)
Background and aims: The majority of colorectal cancers arise from detectable adenomatous or serrated lesions. Here we demonstrate how deregulated alternative splicing of CD44 gene in diseased colon mucosa results in downregulation of standard isoform of CD44 gene (CD44s) and upregulation of variant isoform CD44v8-10. Our aim is to show that upregulation of CD44v8-10 isoform is a possible marker of precancerous lesion in human colon. Methods: We analysed pairs of fresh biopsy specimen of large intestine in a cohort of 50 patients. We studied and compared alternative splicing profile of CD44 gene in colon polyps and adjoined healthy colon mucosa. We performed end-point and qRT PCR, western blotting, IHC staining and flow cytometry analyses. Results: We detected more than five-fold overexpression of CD44v8-10 isoform and almost twenty-fold downregulation of standard isoform CD44s in colon polyps compared to adjoined healthy tissue with p = 0.018 and p < 0.001 in a cohort of 50 patients. Our results also show that aberrant splicing of CD44 occurs in both biologically distinct subtypes of colorectal adenoma possibly in ESRP-1 specific manner. Conclusion: 92% of the colon polyp positive patients overexpressed CD44v8-10 isoform in their colon polyps while only 36% of them had positive fecal occult blood test which is currently a standard non-invasive screening technique. Impact: We believe that our results are important for further steps leading to application of CD44v8-10 isoform as a biomarker of colorectal precancerosis in non-invasive detection. Early detection of colon precancerosis means successful prevention of colorectal carcinoma.
Keywords: kolon; kolorektální nádory; Colonic Polyps; colon polyps; Colorectal Neoplasms; Colon; lidé; polypy tlustého střeva; colorectal precancerosis; prognóza; CD44 isoforms; Hyaluronan Receptors; nádorové biomarkery; Protein Isoforms; antigeny CD44; Prognosis; Biomarkers, Tumor; protein - isoformy; RNA splicing; cancer markers; Humans